ALMA–IRDC: dense gas mass distribution from cloud to core scales. Issue 3 (22nd March 2021) - Barnes, A T; Henshaw, J D; Fontani, F; Pineda, J E; Cosentino, G; Tan, J C; Caselli, P; Jiménez-Serra, I; Law, C Y; Avison, A; Bigiel, F; Feng, S; et al.
ABSTRACT: Infrared dark clouds (IRDCs) are potential hosts of the elusive early phases of high mass star formation (HMSF). Here, we conduct an in-depth analysis of the fragmentation properties of a sample of 10 IRDCs, which have been highlighted as some of the best candidates to study HMSF within the Milky Way. To do so, we have obtained a set of large mosaics covering these IRDCs with Atacama Large Millimeter/submillimeter Array (ALMA) at Band 3 (or 3 mm). These observations have a high angular resolution (∼3 arcsec; ∼0.05 pc), and high continuum and spectral line sensitivity (∼0.15 mJy beam −1 and ∼0.2 K per 0.1 km s −1 channel at the N2 H +  (1 − 0) transition). From the dust continuum emission, we identify 96 cores ranging from low to high mass ( M  = 3.4−50.9 M⊙ ) that are gravitationally bound (αvir  = 0.3−1.3) and which would require magnetic field strengths of B  = 0.3−1.0 mG to be in virial equilibrium. We combine these results with a homogenized catalogue of literature cores to recover the hierarchical structure within these clouds over four orders of magnitude in spatial scale (0.01–10 pc). Using supplementary observations at an even higher angular resolution, we find that the smallest fragments (<0.02 pc) within this hierarchy do not currently have the mass and/or the density required to form high-mass stars. None the less, the new ALMA observations presented in this paper have facilitated the identification of 19 (6 quiescent and 13 star-forming) cores that retain >16 M⊙ without further fragmentation. These high-mass cores contain trans-sonic non-thermal motions, are kinematically sub-virial, and require moderate magnetic field strengths for support against collapse. The identification of these potential sites of HMSF represents a key step in allowing us to test the predictions from high-mass star and cluster formation theories.